A simplified non-coplanar volumetric modulated arc therapy for the whole brain radiotherapy with hippocampus avoidance - Xue, Juan; Jin, Sunian; Zhang, Hongtao; Zou, Kun; Sheng, Junxiu; Tang, Jinhai; Zhao, Wanying; Yang, Ping; Tang, Lufan; Lv, Xiupeng; Lv, Li (Frontiers in Oncology, 2023)
Purpose: To evaluate the feasibility of using a simplified NC-VMAT and investigate its dosimetric advantages compared with IMRT and C-VMAT for HA-WBRT. Methods: Ten patients with BM were included for HA-WBRT. Three treatment plans were generated for each case using IMRT, C-VMAT, and NC-VMAT, respectively. Results: The dosimetric results of the three techniques complied roughly with the RTOG 0933 criteria. After dose normalization, the V30Gy of WB-PTV in all the plans was controlled at 95%. HI of WB-PTV was significantly reduced in NC-VMAT (0.249 ± 0.017) over IMRT (0.265 ± 0.020, p=0.005) and C-VMAT (0.261 ± 0.014, p=0.020). In terms of CI, NC-VMAT could provide a value of 0.821 ± 0.010, which was significantly superior to IMRT (0.788 ± 0.019, p＜0.001). According to D2% of WB-PTV, NC-VMAT could provide a value of 35.62 ± 0.37Gy, significantly superior to IMRT (36.43 ± 0.65Gy, p＜0.001). According to D50% of WB-PTV, NC-VMAT can achieve the lowest value of 33.18 ± 0.29Gy, significantly different from IMRT (33.47 ± 0.43, p=0.034) and C-VMAT (33.58 ± 0.37, p=0.006). Regarding D2%, D98%, and Dmean of hippocampus, NC-VMAT could control them at 15.57 ± 0.18Gy, 8.37 ± 0.26Gy and 11.71 ± 0.48Gy, respectively. D2% and Dmean of hippocampus for NC-VMAT was significantly lower than IMRT (D2%: 16.07 ± 0.29Gy, p=0.001 Dmean: 12.18 ± 0.33Gy, p＜0.001) and C-VMAT (D2%: 15.92 ± 0.37Gy, p=0.009 Dmean: 12.21 ± 0.54Gy, p＜0.001). For other organs-at-risk (OARs), according to D2% of the right optic nerves and the right lenses, NC-VMAT had the lowest values of 31.86 ± 1.11Gy and 7.15 ± 0.31Gy, respectively, which were statistically different from the other two techniques. For other organs including eyes and optic chiasm, NC-VMAT could achieve the lowest doses, different from IMRT statistically. Conclusions: The dosimetry of the three techniques for HA-WBRT could roughly comply with the proposals from RTOG 0933. After dose normalization (D95%=30Gy), NC-VMAT could significantly improve dose homogeneity and reduce the D50% in the brain. Besides, it can reduce the D2% of the hippocampus, optic nerves, and lens. With this approach, an efficient and straightforward plan was accomplished.